Porcine alveolar macrophage polarization is involved in inhibition of porcine reproductive and respiratory syndrome virus (PRRSV) replication - WANG, Longtao (J Vet Med Sci, 2017)
Macrophage polarization is a process by which macrophages acquire a distinct phenotypic and functional profile in response to microenvironmental signals. The classically and alternatively activated (M1 and M2, respectively) macrophage phenotypes are defined by the specific molecular characteristics induced in response to prototypic pro- and anti-inflammatory cues. In this study, we used LPS/IFN-γ and IL-4 to stimulate porcine alveolar macrophages (PAMs) in vitro and investigated the expression changes of several novel markers during macrophage polarization. Notably, we found that LPS/IFN-γ-stimulated PAMs express prototypical M1 molecules, whereas IL-4-stimulated PAMs express M2 molecules. We also demonstrated that replication of the highly pathogenic porcine reproductive and respiratory syndrome virus (PRRSV) strain HuN4 was effectively suppressed in LPS/IFN-γ-stimulated M1 PAMs (M1 type), but not IL-4 stimulated M2 PAMs. However, this was not observed with the classic, less pathogenic CH-1a strain. Moreover, we found that M2 marker expression gradually increased after PAM infection with PRRSV, whereas no significant changes were found with M1 marker expression, suggesting that PRRSV infection may skew macrophage polarization towards an M2 phenotype. Finally, we found that anti-viral cytokine expression was significantly higher in M1 macrophages than in M2 macrophages or nonpolarized controls. In summary, our results show that PRRSV replication was significantly impaired in M1 PAMs, which may serve as a foundation for further understanding of the dynamic phenotypic changes during macrophage polarization and their effects on viral infection.